Housing tenure, energy expenditure and the principal-agent problem in Australia - Wood, Gavin; Ong, Rachel; McMurray, Clinton (Pacific Rim Real Estate Society Conference, 2011)
The Australian Government is currently committed to delivering a cut in carbon emissions in response to climate change concerns. In this context, much research and policy attention has been given in recent times to the energy efficiency of new housing, much less to the existing housing stock. It is generally acknowledged that the energy efficiency of existing homes can be greatly improved with the use of existing technologies, but there are significant barriers to its uptake. This paper focuses attention on one such barrier – the principle-agent problem present in the private rental market. While landlords are generally responsible for the purchase of many energy consuming household appliances, tenants are responsible for the purchase of energy. These split incentives lead to an energy efficiency gap. Applying a hedonic regression model to the 2006 wave of the Household Income and Labour Dynamics in Australia survey (HILDA) we attempt to estimate the magnitude of the principle-agent problem by modelling energy expenditure as a function of housing tenure, dwelling type, location and other socio-demographic variables. We fail to find evidence in support of the split incentives hypothesis in Australia and offer some reasons for why this may be the case.